Brain color-coded diffusion imaging: Utility of ACPC reorientation of gradients in healthy subjects and patients - Ouachikh, Omar; Chaix, Remi; Sontheimer, Anna; Coste, Jerome; Aider, Omar Ait; Dautkulova, Aigerim; Abdelouahab, Kamel; Hafidi, Aziz; Salah, Maha Ben; Pereira, Bruno; Lemaire, Jean-Jacques (Computer methods and programs in biomedicine, 2024)
•The orientation of diffusion gradients depends on MRI manufacturer.•Interpretation of diffusion color encoded (DCE) maps depends on brain orientation.•The ACPC system reliably reflects the anatomic physiologic brain orientation.•The most important angle mismatch between brain and gradients was the pitch.•ACPC reorientation of gradients improved the interpretation of DCE maps. The common structural interpretation of diffusion color-encoded (DCE) maps assumes that the brain is aligned with the gradients of the MRI machine. This is seldom achieved in the field, leading to incorrect red (R), green (G) and blue (B) DCE values for the expected orientation of fiber bundles. We studied the virtual reorientation of gradients according to the anterior commissure – posterior commissure (ACPC) system on the RGB derivatives. We measured mean ± standard deviation of average, standard deviation, skewness and kurtosis of RGB derivatives, before (rO) and after (acpcO) gradient reorientation, in one healthy-subject group with head routinely positioned (HS-routine), and in two patient groups, one with essential tremor (ET-Opti), and one with Parkinson's disease (PD-Opti), with head position optimized according to ACPC before acquisition. We studied the pitch, roll and yaw angles of reorientation, and we compared rO and acpcO conditions, and groups (ad hoc statistics). Pitch (maximum in the HS-routine group) was greater than roll and yaw. After reorientation of gradients, in the HS-routine group, DCE average increased, and Stddev, skewness and kurtosis decreased; R, G and B average increased, and R and B skewness and kurtosis decreased. By contrast, in the ET-Opti group and the PD-Opti group, R, G and B, average and Stddev increased, and skewness and kurtosis decreased. In both rO and acpcO conditions, in the ET-Opti and PD-Opti groups, average and standard deviation were higher, while skewness and kurtosis were lower. DCE map interpretability depends on brain orientation. Reorientation realigns gradients with the anatomic and physiologic position of the head and brain, as exemplified.